RELEVANSI PEMIKIRAN PAULO FREIRE DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SMPK ILE BURA - Faustinus Yostian Pati; Bartolomeus Kewaama Lein; Flavianus Jordy Pati Klore (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to analyze the relevance of Paulo Freire’s thought to the implementation of the Merdeka Curriculum at SMPK Ile Bura, particularly in relation to dialogical learning practices, student participation, the development of critical consciousness, and implementation challenges in a rural school context. This study employed a descriptive qualitative approach. Data were collected through in-depth semi-structured telephone interviews with five informants selected purposively, consisting of four subject teachers of History, Indonesian Language, Biology, and Catholic Religious Education, as well as one school principal. The data were analyzed using reflective thematic analysis through the stages of data reduction, theme categorization, interpretation, and conclusion drawing. The findings show that the implementation of the Merdeka Curriculum at SMPK Ile Bura is relevant to Freire’s thought, particularly in the transformation of the teacher’s role from a center of knowledge into a learning facilitator. Learning practices have begun to develop through group discussions, presentations, question-and-answer activities, reflections on lived experiences, and the connection of learning materials with social issues surrounding students. The main finding of this study is the tension between the ideals of the Merdeka Curriculum, which emphasizes learning freedom, and the reality of rural schools that still face limited digital facilities, low access to technology, passive learning cultures, and teachers’ administrative burdens. This study concludes that Paulo Freire’s thought can serve as a relevant philosophical foundation for implementing the Merdeka Curriculum, but it requires structural support, equitable educational infrastructure, and strengthened teacher capacity so that education can truly become a praxis of liberation. ABSTRAK Penelitian ini bertujuan menganalisis relevansi pemikiran Paulo Freire dalam implementasi Kurikulum Merdeka di SMPK Ile Bura, terutama pada praktik pembelajaran dialogis, partisipasi siswa, pengembangan kesadaran kritis, dan tantangan penerapannya di sekolah pedesaan. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Data dikumpulkan melalui wawancara mendalam semi-terstruktur melalui telepon dengan lima informan yang dipilih secara purposive, yaitu empat guru mata pelajaran Sejarah, Bahasa Indonesia, Biologi, dan Agama Katolik, serta satu kepala sekolah. Data dianalisis menggunakan analisis tematik reflektif melalui tahap reduksi data, pengelompokan tema, interpretasi, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi Kurikulum Merdeka di SMPK Ile Bura relevan dengan pemikiran Freire, khususnya dalam perubahan peran guru dari pusat pengetahuan menjadi fasilitator pembelajaran. Praktik pembelajaran mulai berkembang melalui diskusi kelompok, presentasi, tanya jawab, refleksi pengalaman hidup, dan pengaitan materi dengan persoalan sosial di sekitar siswa. Temuan utama penelitian ini adalah adanya ketegangan antara idealisme Kurikulum Merdeka yang menekankan kebebasan belajar dan realitas sekolah pedesaan yang masih menghadapi keterbatasan fasilitas digital, rendahnya akses teknologi, budaya belajar pasif, serta beban administratif guru. Penelitian ini menyimpulkan bahwa pemikiran Paulo Freire dapat menjadi landasan filosofis yang relevan bagi implementasi Kurikulum Merdeka, tetapi memerlukan dukungan struktural, pemerataan infrastruktur pendidikan, dan penguatan kapasitas guru agar pendidikan benar-benar menjadi praksis pembebasan.